2013
DOI: 10.1038/ajg.2012.470
|View full text |Cite
|
Sign up to set email alerts
|

Rendezvous Cannulation Technique Reduces Post-ERCP Pancreatitis: A Prospective Nationwide Study of 12,718 ERCP Procedures

Abstract: Rendezvous bile duct cannulation during ERCP reduces the risk of PEP from 3.6 to 2.2% compared with conventional biliary cannulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 33 publications
3
45
0
4
Order By: Relevance
“…However, postoperative asymptomatic hyperamylasemia presented in 1 case of group 1 and 2 cases in group 2 in our study, of which we thought was a result from balloon dilatation (12 mm) for retrieval of large stones, as similar findings was described in other reports [6, 10, 14]. The incidence of complications was of no significant difference between the two groups, suggesting that there is no increased risk associated with the modified technique.…”
Section: Discussionsupporting
confidence: 85%
“…However, postoperative asymptomatic hyperamylasemia presented in 1 case of group 1 and 2 cases in group 2 in our study, of which we thought was a result from balloon dilatation (12 mm) for retrieval of large stones, as similar findings was described in other reports [6, 10, 14]. The incidence of complications was of no significant difference between the two groups, suggesting that there is no increased risk associated with the modified technique.…”
Section: Discussionsupporting
confidence: 85%
“…23 www.tandfonline.compromise in eliminating disease symptoms and promoting mucosal healing in both adult and pediatric IBD patients. [39][40][41] Although preliminary analyses suggest that one beneficial effect of the SCD is to increase bacterial diversity in the intestinal microbiome, 43 it is still unknown which of the eliminated dietary components promote disease or their mechanism(s) of action. We postulate that dietary additives, such as MDX, are potentiators of disease and, if true, could explain the suggested efficacy of seemingly disparate diets (i.e.…”
Section: Cultivating a Greater Understanding Of The Effect Of Diet Onmentioning
confidence: 99%
“…In this study, there was no significant difference in complications between procedures performed by endoscopists who had and had not been on prior ND, but an extended procedure time has been reported to be a risk factor for post-ERCP pancreatitis[18,19]. In addition, Pan et al[20] found that a cannulation challenge to the common bile duct within 10 min gave the best results in trials by trainees.…”
Section: Discussionmentioning
confidence: 67%